A Protocol to Reduce Interobserver Variability in the Computed Tomography Measurement of Orbital Floor Fractures. Issue 4 (December 2015) - Ang, ChuanHan; Low, JinRong; Shen, JiaYi; Cai, Elijah Zheng Yang; Hing, Eileen Chor Hoong; Chan, YiongHuak; Sundar, Gangadhara; Lim, ThiamChye
Orbital fracture detection and size determination from computed tomography (CT) scans affect the decision to operate, the type of surgical implant used, and postoperative outcomes. However, the lack of standardization of radiological signs often leads to the false-positive detection of orbital fractures, while nonstandardized landmarks lead to inaccurate defect measurements. We aim to design a novel protocol for CT measurement of orbital floor fractures and evaluate the interobserver variability on CT scan images. Qualitative aspects of this protocol include identifying direct and indirect signs of orbital fractures on CT scan images. Quantitative aspects of this protocol include measuring the surface area of pure orbital floor fractures using computer software. In this study, 15 independent observers without clinical experience in orbital fracture detection and measurement measured the orbital floor fractures of three randomly selected patients following the protocol. The time required for each measurement was recorded. The intraclass correlation coefficient of the surface area measurements is 0.999 (0.997–1.000) with p -value < 0.001. This suggests that any observer measuring the surface area will obtain a similar estimation of the fractured surface area. The maximum error limit was 0.901 cm 2 which is less than the margin of error of 1 cm 2 in mesh trimming for orbital reconstruction. The average duration required for each measurement was 3 minutes 19 seconds (ranging from 1 minute 35 seconds to 5 minutes). Measurements performed with our novel protocol resulted in minimal interobserver variability. This protocol is effective and generated reproducible results, is easy to teach and utilize, and its findings can be interpreted easily.